CFD analysis of Hydrodynamic Characteristics of Tidal Current Turbines - Loh, Ai Choong; Yongson, Ooi; Samylingam, Lingenthiran; Rilling, Dirk; Kok, Chee Kuang; Chen, Gooi Mee (Engineering, Technology & Applied Science Research, 2025)
Malaysia uses mostly fossil fuels for electricity generation. This study examines the hydrodynamic performance of tidal turbines, especially designed for three sites in East Malaysia: Sibu, Kota Belud, and Pulau Jambongan. The performance characteristics of these site-specific turbines were analyzed with the use of Computational Fluid Dynamics (CFD) and were validated with experimental benchmarks. The results indicate that a power coefficient greater than 0.4 is possible at Tip Speed Ratios (TSR) between 4 and 7, with the best performance recorded at TSR 5 for inflow velocities between 0.75 and 1.35 m/s. This study highlights the potential of tidal energy as a sustainable resource for Malaysia and provides a basis for further development in the region.